Hasil Analisis Peran Gojek dalam Menggenggam Pasar dengan Strategi Pemasaran Digital - Stafrezar, Burhan (PUTRA JAWA PUBLISHER, 2024)
This research analyses Gojek's role in maintaining market share through the implementation of innovative digital marketing strategies. As the leading on-demand service platform in Indonesia, Gojek utilises various digital channels, such as social media, online advertising, and customer data analytics, to strengthen its presence in the market. This study uses a qualitative approach with a descriptive analysis method to evaluate the effectiveness of digital marketing strategies implemented by Gojek in creating brand awareness, attracting new customers, and building consumer loyalty. The results of the analysis show that Gojek's success is driven by an integrated digital marketing approach, including data-driven service personalisation, promotion through social media, and innovation in service features such as cashback and loyalty programs. In addition, Gojek's ability to adapt to the needs of local consumers provides a significant competitive advantage amid increasingly fierce market competition.This study concludes that digital marketing strategies play a key role in Gojek's success in maintaining and expanding market share. The findings provide important insights for other technology companies looking to maximise the potential of digital marketing in the face of market challenges.